Short Total Synthesis of Ajoene. Issue 38 (19th August 2018) - Silva, Filipa; Khokhar, Shaista S.; Williams, Danielle M.; Saunders, Robert; Evans, Gareth J. S.; Graz, Michael; Wirth, Thomas
Abstract: We describe a short total synthesis of ajoene, a major biologically active constituent of garlic. The instability of allicin as the only other known alternative starting material has led to the development of a reliable procedure for the synthesis of ajoene from simple building blocks that is also suitable for upscale operations. Abstract : Making garlic : An efficient total synthesis of ajoene from easily available starting materials is reported. Upscaling of the procedure enabled the synthesis of ajoene in larger amounts.